The hospital : the inside story - Nwora, Christle (The inside story, 2022)
"It's another busy day at the hospital! Meet doctors and nurses, ride in an ambulance, and discover the magic of medicine in this nonfiction story for kids. This book is perfect for any child who is nervous about a trip to the hospital. Dr. Christle Nwora takes readers behind the scenes to meet the incredible people who keep you healthy, from surgeons to mental health therapists. Dr. Nwora also explains the science behind how things work, from X-rays to operating theaters. Set over the course of one day, you'll follow different patients through their trip to the hospital, including: A couple having a new baby A boy getting a cast for his broken arm A woman on her way to have an operation As you turn the pages of this book, illustrated by Ginnie Hsu, marvel at the way hospital staff work together-see who prepares the food in the cafeteria, what goes on in the laundry room, and what doctors chat about during their coffee break. Once you've read this book you'll realize hospitals are full of heroes!"--